Jurnal Penyuluhan: Peranan Penyuluh Swadaya dalam Mendukung Intensifikasi Kakao di Kabupaten Sigi Provinsi Sulawesi Tengah - Riana, Ninuk Purnaningsih, Arif Satria (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
Self-support extension agents is the main actors who are successful in their business and other community members with his own conscience willing and able to become a counselor. The role of self support extension agents is needed to support the role of civil servants as an alternative that is deemed in accordance with UU No. 16 2006th.